Physiological Study of the Cuy or guinea pig (Cavia sp.) Cold and Hot in Environment - Sánchez Arízaga, Williams (Revista Universidad de Guayaquil, 2011)
The guinea pig (Cavia sp.) It is a very representative of organisms Homeotherms because it maintains a direct relationship with the environment. Thermoregulation of these organisms is affected in several of their physiological conditions by reactions of various kinds. So by comparing the same body temperatures we have subjected to different environments (cold and hot). Noting that in cold temperatures, the individual is at low ambient temperatures from 13 to 19 º C the guinea pig (Cavia sp.) Decreased locomotion and therefore slows your heartbeat, leading to maintain a quiescent state, hibernation or sleep. Instead, when the individual is at high ambient temperatures of 34 to 38 ° C maintains higher locomotion condition or state undergoes several physiological behavior characteristic of homeotherms.